A pilot study of virtual support for grief: Feasibility, acceptability, and preliminary outcomes. (August 2017) - Knowles, Lindsey M.; Stelzer, Eva-Maria; Jovel, Krystal S.; O'Connor, Mary-Frances
Abstract: Social support and grief education can ameliorate mental and physical health risks in widow(er)s. However, barriers often prevent older individuals from attending support groups. This controlled pilot study examined the feasibility and acceptability of an online, real-time, interactive virtual reality (VR) support group for widow(er)s, and assessed the preliminary efficacy of the VR support group for improving psychosocial outcomes and sleep quality compared to an active control grief education website. Thirty widow(er)s ( M age  = 67.0, SD  = 11.0) participated in an 8-week VR support group or accessed a grief education website. Participants completed self-report measures of depression, grief intensity, grief cognitions, yearning, loneliness, perceived stress and sleep quality at three time points. Participant attrition and self-report indicated that both interventions were feasible and acceptable. Both groups showed significant improvements in grief severity, grief cognitions, yearning, loneliness, perceived stress, and global sleep quality across study time points. However, only widow(er)s in the VR support group showed a significant improvement in depression across time. This study demonstrates the feasibility, acceptability and preliminary efficacy of an accessible and low-cost online support format for widow(er)s. Highlights: Significant improvements in depressive symptoms in Virtual Reality (VR) group. High levels of social support experienced among VR support group participants. Improved psychosocial outcomes and sleep quality in VR and active control group. Feasibility and acceptability of a VR support group for older widow(er)s.